Re-writing Ariadne: following the thread of literary and artistic representations of Ariadne’s abandonment - Schoess, A (2018)
This thesis takes Ariadne's abandonment as a case study in order to examine the literary processes of reception that underlie the transmission of classical myth in different eras and cultural contexts — from Classical Antiquity through the Italian Renaissance. Rather than focusing on the ways in which visual representations of Ariadne relate to literary treatments, it draws attention to the literary reliance on a cultural framework, shared by writer and reader, that enables dynamic storytelling. It argues that literary variation of the myth is central to its successful transmission, not least because it allows for appropriations and adaptations that can be made to fit new social and religious parameters, such as Christian conventions in the Middle Ages. In focusing on the important role played by the visual arts in the classical tradition, this research further challenges the still prevalent misconception that the visual arts are secondary to literature, and refutes the common assumption that the relationship between image and text is unidirectional. It highlights the visual impulses leading to paradigm shifts in the literary treatment of the abandonment narrative, and examines the ways in which writers engage with the visual tradition in order to re-shape the ancient narrative. Throughout, attention is drawn to the visual and cultural framework shared by ancient writers and readers, and to the lack of engagement with this framework in traditional classical scholarship. Through its focus on the literary narratives' visuality and mutability, this thesis offers a new paradigm for studying classical myth and its reception.